Investigating the role of policies in the sustainable management of East Kolkata wetlands - Pawan Kumar Yadav; Priyanka Jha; Md Saharik Joy; Taruna Bansal; Pankaj Rawat; Shehnaz Begam; Abhishek Kumar Singh (Discover Global Society)
Abstract The East Kolkata Wetlands (EKW), a Ramsar site, face challenges due to rapid urbanization, fragmented governance, and inadequate policy enforcement. This study examines the legal and policy frameworks governing EKW, identifying gaps between formulation and implementation, assessing community participation, and recommending governance reforms. A qualitative approach, involving a review of regulations, field surveys capturing local narratives, document analysis, and thematic coding, was used. The findings revealed enforcement gaps, intergovernmental collaboration issues, regulatory inconsistencies, and insufficient community involvement to be barriers to effective conservation. Survey respondents highlighted the disconnect between policy objectives and ground realities, emphasizing the need for stricter enforcement, transparent governance, and a balanced approach to urban development. It suggests that local conservation efforts should be aligned with international frameworks, such as the Ramsar Convention and UN Sustainable Development Goals, to improve wetland resilience. This suggests that the EKW can serve as a blueprint for sustainable urban wetland management, balancing development, and conservation.